2012
DOI: 10.1371/journal.pone.0032122
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Test for Detection of Urogenital Chlamydia in Women Shows Low Sensitivity. A Performance Evaluation Study in Two Clinics in Suriname

Abstract: BackgroundIn general, point-of-care (POC) tests for Chlamydia trachomatis (Ct) show disappointing test performance, especially disappointing sensitivity results. However, one study sponsored by the manufacturer (Diagnostics for the Real World) reported over 80% sensitivity with their Chlamydia Rapid Test (CRT). We evaluated the performance of this CRT in a non–manufacturer-sponsored trial.MethodsBetween July 2009 and February 2010, we included samples from 912 women in both high- and low-risk clinics for sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 26 publications
4
46
0
1
Order By: Relevance
“…Although not excluded, most MG infections are symptomatic; the organism is found in only 5–6% of asymptomatic men 16 17. Likewise, urogenital infections caused by herpes simplex virus and adenovirus are to cause symptoms more frequently than on average in bacterial related NGU 5. These non-detected pathogens can further explain the low specificity found in the study.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although not excluded, most MG infections are symptomatic; the organism is found in only 5–6% of asymptomatic men 16 17. Likewise, urogenital infections caused by herpes simplex virus and adenovirus are to cause symptoms more frequently than on average in bacterial related NGU 5. These non-detected pathogens can further explain the low specificity found in the study.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, several companies have developed lipopolysaccharide based POC tests that provide rapid results for the detection of CT. However, low sensitivity (25–65%) precludes more widespread use in clinical settings 4 5…”
Section: Introductionmentioning
confidence: 99%
“…In the same samples, the number of human leucocyte antigen (HLA) copies was determined using a quantified serial dilution. The chlamydia/human cell ratio (chlamydial DNA concentration) was calculated as described previously16 and expressed as IFU/100 million HLA copies. As the majority of PhCT samples tested negative in the less sensitive real-time PCR, analysis on a linear scale had very limited power.…”
Section: Methodsmentioning
confidence: 99%
“…Van Dommelen et al evaluated the performance of 3 CT POC tests on vaginal swabs compared with CT PCR and found that with CT PCR as the reference standard, the sensitivities of the Handilab-C test, Biorapid CHLA-MYDIA Ag test, and QuickVue Chlamydia test were 12%, 17%, and 27%, respectively, whereas the specificities were 92%, 93.5%, and 99.7%, respectively [60]. Van der Helm et al evaluated the performance of the Chlamydia Rapid Test on vaginal swabs compared with CT TMA and found that with TMA as the reference standard, the Chlamydia Rapid Test had a sensitivity of 41.2% and specificity of 96.4%; they further stratified sensitivity by CT load and found that the sensitivity of the Chlamydia Rapid Test was 12.5% with a low CT load and 73.5% with a high CT load [61]. Nadala et al evaluated the performance of the Chlamydia Rapid Test on urine in men compared with CT PCR and found that with PCR as the reference standard, the Chlamydia Rapid Test had a sensitivity of 82.6% and specificity of 98.3% [62]; however, women were not studied, and some authors were affiliated with the Chlamydia Rapid Test manufacturer.…”
Section: Discussionmentioning
confidence: 99%